Diffusion and Adoption of the Chorkor Smoker In Tema U Compound - Buadi, D. K. (University of Ghana, 1992)
The main objective of the research is to study the processes in the introduction of the Chorkor smoker and to determine the factors which the fishsmokers consider in the adoption of the Chorkor smoker. Qualitative research methodology was used for the study. The main data gathering device was individual interview using an interview guide. Data were collected from the individual fishmokers and the extension agents. The data were coded and analyzed. The results are: (1) the influence of the larger community is an important factor influencing the adoption of the Chorkor smoker. They are deterrents to adoption. (2) The source from which fishsmokers seek information about innovations and the extent to which they seek information are important factors which influenced the innovativeness of the extension-aided adopters (3) information provided by change agents and/or opinion leaders are either lost or given! different rheanings/interpretations by clientele (4) the meetings and demonstrations helped the fishsmokers to develop favourable attitude towards the Chorkor smoker (5) groups offer an effective medium for the introduction and acceptance of innovations (6) the size of a fishsmoker's enterprise is ar important factor in the adoption of the Chorkor smoker (7) the age and education of respondents are not important factors influencing innovativeness of those who obtained extension assistance,(8) age is not an important factor influencing the adoption of the Chorkor smoker by the three groups namely adopters who had extension contact, adopters who did not benefit from extension contact and non-adopters (9) the two attributes, savings on fuelwood and fast rate of fish smoking, are the most important attributes which favoured the adoption of the Chorkor smoker. The following recomendations were also provide to assist change agents (1) extension agents must endeavour to know the fish smoker in her social context (2) education should be carried out to allay the fears of fishsmokers and (3) extension should target large scale fishsmokers when introducing the Chorkor smoker into a new community
Thesis (MPhil.) - University of Ghana, 1992
Keywords: Fish smokers; Fish monkers; Extension Teaching Methods